Circulating cf-miRNA as a more appropriate surrogate liquid biopsy marker than cfDNA for ovarian cancer - Gahlawat, Aoife Ward; Witte, Tania; Sinn, Peter; Schott, Sarah (Scientific reports, 2023)
Ovarian cancer (OC) is an aggressive disease, primarily diagnosed in late stages with only 20% of patients surviving more than 5 years. Liquid biopsy markers have great potential to improve current diagnostic and prognostic methods. Here, we compared miRNAs and DNA methylation in matched plasma, whole blood and tissues as a surrogate marker for OC. We found that while both cfDNA and cf-miRNAs levels were upregulated in OC compared to patients with benign lesions or healthy controls, only cf-miRNA levels were an independent prognosticator of survival. Following on our previous work, we found members of the miR-200 family, miR-200c and miR-141 to be upregulated in both plasma and matched tissues of OC patients which correlated with adverse clinical features. We could also show that the upregulation of miR-200c and -141 correlated with promoter DNA hypomethylation in tissues, but not in plasma or matched whole blood samples. As cf-miRNAs are more easily obtained and very stable in blood, we conclude that they might serve as a more appropriate surrogate liquid biopsy marker than cfDNA for OC.